If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 2y + 2 Reorder the terms: -2 = 2 + 2y Solving -2 = 2 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -2 + -2y = 2 + 2y + -2y Combine like terms: 2y + -2y = 0 -2 + -2y = 2 + 0 -2 + -2y = 2 Add '2' to each side of the equation. -2 + 2 + -2y = 2 + 2 Combine like terms: -2 + 2 = 0 0 + -2y = 2 + 2 -2y = 2 + 2 Combine like terms: 2 + 2 = 4 -2y = 4 Divide each side by '-2'. y = -2 Simplifying y = -2
| 5c(2d+E)= | | 5(1)+y=7 | | 5(0)+y=7 | | x=10-62 | | x^2=467 | | -1+3=-4+18x | | 2x+9=-33-5x | | x*x/12+34=666 | | x.x/12+34=666 | | 3(2)+y=0 | | -8+2x=-6+8x | | 3/5x/2=234 | | 2(1)+y=0 | | 3/5x/2=6x | | 15/2= | | (7+u)(3u-2)=0 | | y^2-6y+36=0 | | X=-3x*-x | | (10/3)(37/7) | | -3(v+3)=-8v+11 | | -15=13+3f | | 3x+1y=17 | | -28=3y-7 | | 15-4d=31 | | 9*x+17-7=2+26 | | 2(0)-y=5 | | 5(6p-9)=26 | | 4x-34=180-4x-34 | | 4x-2+10=3*6 | | -2(3c+10)=8 | | 4y+5=5y+15 | | u/13=3/17 |